Achieving good proximal contacts with derect composites. - Segarra, Armin G. (The Journal of the Philippine Dental Association)
This article gives an overview of interproximal contact anatomy and physiology. Current armamentaria and techniques available to the practitioner in achieving good proximal contacts with direct composite resin restorations are also reviewed.